The Improvement of Architecture Studio Classroom with Daylighting - Diptya Anggita (JURNAL ARSITEKTUR, 2018)
Architecture studio classroom is the primary facility for an architecture major, where the most activity isdrawing. It needs illumination extra compared other activities such as writing and reading. Most of studentsspend more time in studio classroom and used it more than seven hours per day. It means a good design of astudio classroom is very important to fullfill the need of architecture student, such as illumination level. Someresearches shown that using daylight in classroom is a good solution for keeping the health, psychology, andproductivity of the student. So, the implementation of daylight is very important to be considered. Moreover,another reason of using daylight is for saving the energy for electrical consumption.This research strengthen about the importance of daylight in an architecture studio classroom against theactivity of a student and to showed the daylight condition by taking a case study of Architecture Department,Faculty of Engineering, Pancasila University. There are several stages in this reasearh. First, is evaluatingthe daylight condition of architecture studio classroom. The evaluation contained observation, daylightcalculation, and interview of architecture student. Second, is about the discussion based on the result ofevaluation of daylight condition and theories of daylight. The last stage, is design concept that will become asolid foundation for the improvement of studio classroom.1) Kwok Alison, Grondzik Walter,2007 . The Green Studio Handbook.Oxford UK. Elsevier Inc2) Karlen Mark, Benya James, 2004. Lighting Design Basics. NewJersey. John Wiley & Son.3) Edward, L., Torcellini, P.,2002. A Literature Riview of the Effects ofNatural Light on Building Occupants. Colorado. NREL.4) Andre, Erik., Schade, Jutta., 2002. Daylighting by Optical Fiber.Lulea University Of Tecnology. Department of EnvironmentalEngineering.5) Garcia, Veronica, H., 2006. Innovative Daylighting Systems forDeep-Plan ommercial Buildings. School of Design. QuenslandUniversity of Technology.6) Dr. Apple Lok Shun Chan. DAYLIGHT CALCULATION7) Deepa Ananthakrishnan., Jason Degaesteker. Alculating theDaylight Factor.8) Wulfinghoff, D.R, 1999. Control And Use of Sunlight.